Quality of Life Gains for Special Athletes in the Turkish Athletics Championship: A Study on Parent Perspectives (2023) - Karadag, Haci; Karatas, Ozgur; Dogar, Yahya; Ilkim, Mehmet; Yavuz, Cumaali; Celik, Talip; Cakir, Veli Ozan (Univ Illes Balears, 2024)
This study examines the effects of sports involvement on the well-being of individuals with Down Syndrome who participated in the 2022 Turkish Athletics Championship, as reported by their parents. The championship was organised by the Turkish Special Athletes Sports Federation. Using a qualitative case study design, we thoroughly explore individual experiences, perceptions, and the current situation. Criterion sampling, a method of purposeful sampling, was employed to select participants. The participants were selected using purposive criterion sampling. Information on life changes for the athletes was gathered through semi -structured interviews, which were later transcribed and analysed using content analysis. Five main themes were identified: Physical Development, Social Development, Emotional Development, Psycho -Social Health, and Family Life Satisfaction. The focus was on highlighting the enhancements in family dynamics, shared experiences, and the overall well-being of the family. The study demonstrates that engagement in the championship had a significant impact on the athletes' overall well-being and family satisfaction, underscoring the importance of sports in their lives.
Keywords: Sport; Special Athletes; Down Syndrome; Quality of Life